PDK1-mTOR signaling pathway inhibitors reduce cell proliferation in MK2206 resistant neuroblastoma cells. Issue 1 (December 2015) - Qi, Lei; Toyoda, Hidemi; Xu, Dong-qing; Zhou, Ye; Sakurai, Naoto; Amano, Keishirou; Kihira, Kentaro; Hori, Hiroki; Azuma, Eiichi; Komada, Yoshihiro
Abstract Purpose AKT plays a pivotal role in the signal transduction of cancer cells. MK2206, an AKT inhibitor, has been shown to be an effective anti-cancer drug to a variety of cancer cell lines. However, some cancer cells acquire resistance to MK2206 and new strategies to suppress these cell lines remain to be developed. Experimental design Acquired MK-2206-resistant neuroblastoma (NB) cell sublines were induced by stepwise escalation of MK-2206 exposure (4–12 weeks). MTT assay was used to validate cell proliferation. Flow cytometry was performed for cell cycle analysis. Western blot assay was used for cell signaling study. Results MK2206 (5–10 µmol) significantly suppressed cell growth of MK2206 non-resistant NB cells (LAN-1, KP-N-SIFA, NB-19 and SK-N-DZ), but is less efficient in inhibiting that of resistant sublines, even after 2-week MK2206-free incubation. MK2206 acted in mTOR-S6K dependent and independent methods. MK-2206 resistant sublines (LAN-1-MK, KP-N-SIFA-MK, and SK-N-DZ-MK) showed lower IC50 of GSK2334470 (PDK1 inhibitor). The cell growth of all sublines was prohibited by AZD8805 (mTOR inhibitor), with IC50 of AZD8805 3–10 times lower than MK2206 non-resistant cells. The signaling profiles of these resistant sublines were characterized by elevated PDK1-mTOR-S6K activity, accompanying by low phosphorylation of AKT compared with non-resistant counterparts. GSK2334470 and AZD8055 effectively inhibited phosphorylation of PDK1 and mTOR, respectively, and induced higher G0–G1 ratio in LAN-1-MK than that in LAN-1 as well. PDK1 and mTOR inhibitors effected on phosphorylation of GSK3β in some of resistant sublines. Conclusion NB cells can acquire MK2206 resistance after exposure for 4–12 weeks. Resistant cells feature reliance on PDK1-mTOR-S6K pathway and are more sensitive to PDK1 and mTOR inhibitors than the non-resistant counterparts. Thus, suppression of PDK1-mTOR-S6K signaling pathway is an effective way to overcome the MK2206 resistance, and this may be a promising strategy for targeted therapy.